Functional Digestive Disorders in Young Children - Timurovich, Turaev Telman; Telmanugli, Temirov Murojon (European Journal of Life Safety and Stability (2660-9630), 2022)
The article presents generalized information on functional digestive disorders in young children. Epidemiology, causes of development, clinical manifestations, and diagnostic criteria of infantile regurgitation, infantile colic, and functional constipation are described. Special attention is paid to the medical and dietary correction of this pathology in children of the first year of life. The use in practice of the proposed recommendations for feeding children of the first year of life with functional digestive disorders will allow to quickly stop the clinical manifestations of the disease, without resorting to medication.